Tejidos con "denominación de origen extranjera" en el vestido castellano. 1500-1860 - García Fernández, Máximo (Estudios Humanísticos. Historia, 2004)
Este artículo resalta la notable presencia de tejidos y prendas de vestir femeninas y masculinas existentes en los ajuares más ricos-y en los ppopulares-, importados hacia Castilla procedentes de toda Europa (o cuyo nombre se relacinaba con dichas áreas origniarias), y especialmente de Francia o de Inglaterra durante el Setecientos. El tráfico mercantil con el interior español se intensificó notablemtne desde comienzos del siglo XVIII, por lo que el recuento de la tipología de las telas usadas con mayor frecuencia permite conocer la región de origen de tales productos o si se empleaban en Castilla manteniendo la misma denominación original. A partir de los inventarios post-mortem, de comerciantes y las dotes matrimoniales urbanas y rurales, se investiga su comercialización y difusión, y cuándo, dónde y por quiénes fueron más usados, profundizando también en los constantes, numerosos e interesados vínculos mercantiles y culturales que relacionaban a España con la "Europa del Norte". ABSTRACT: The aim of this study is to highlight the abundant presence in Castile of both textiles and of masculine and feminine clothes produced thoughout Europe, particularly of French and England, and imported into Spain, that are to be found in both lower and upper class bridal portions and other sources on household textiles. Included are products that through its names can be related to a foreign origin. Though these imports can already be traced, and they became much more abundant from the 18th century. The inventories after death, the inventories of merchants and shopkeepers, as well as the bridal portions, offer us the tipology of the textiles most frequently used. The analysis also gives us the possibility to identify the regions of origin of those products and whether they were known in Castile by the same denomination of origin. Based on these sources, of both urban and rural origin, we can study more profoundly the spread and commercialisation of those varieties, and when and where they were most used, deepening also into the constants and interested culturals links that conected Spain with the Nord of Europe.